Comparison of 2 effect-site concentrations of remifentanil with midazolam during percutaneous transluminal balloon angioplasty under monitored anesthesia care: A randomized controlled study. Issue 30 (30th July 2021) - Lai, Hou-Chuan; Tsai, Yi-Ting; Huang, Yi-Hsuan; Wu, Ke-Li; Huang, Ren-Chih; Lin, Bo-Feng; Chan, Shun-Ming; Wu, Zhi-Fu
Abstract: Background: Until now, target-controlled infusion of remifentanil with midazolam in percutaneous transluminal balloon angioplasty for dysfunctional hemodialysis fistulas has not been described. Here, we investigate 2 effect-site concentrations of remifentanil with intermittent bolus midazolam for percutaneous transluminal balloon angioplasty under monitored anesthesia care. Methods: A prospective, randomized controlled trial including patients who received a percutaneous transluminal balloon angioplasty between March 2019 and March 2021 was conducted. Group 1 and Group 2 were, respectively, administered an initial effect-site concentration of remifentanil of 1.0 and 2.0 ng/mL by a target-controlled infusion pump with Minto model. In both groups, maintenance of the effect-site concentration of remifentanil was adjusted upward and downward by 0.5 ng/mL with intermittent bolus midazolam to keep the Observer's Assessment of Alertness/Sedation scale between 2 and 4, mean arterial pressure and heart rate at baseline levels ± 30%, and patient comfort (remaining moveless). The primary outcome was to determine the appropriate effect-site concentration of remifentanil for the procedure in terms of patient comfort (remaining moveless), hemodynamic conditions, and adverse events. Secondary endpoints included the total dosage of anesthetics and total times of target-controlled infusion pump adjustments. Results: A total of 40 patients in Group 1 and 40 patients in Group 2 were eligible for analysis. Most parameters were insignificantly different between 2 groups, except Group 1 having higher peripheral oxygen saturation, while local anesthetic injection compared with Group 2. In addition, Group 1 patients had less apnea with desaturation (peripheral oxygen saturation < 90%; 0 vs 6, P  = .034), less remifentanil consumption (189.65 ± 69.7 vs 243.8 ± 76.1 μg, P  = .001), but more intraoperative movements affecting the procedure (14 vs 4; P  = .016), total times of target-controlled infusion pump adjustment [2 (1-4) vs 1 (1–2), P  < .001] compared with Group 2. Conclusion: In percutaneous transluminal balloon angioplasty for dysfunctional hemodialysis fistulas, target-controlled infusion with remifentanil Minto model target 2.0 ng/mL with 3 to 4 mg midazolam use provided appropriate hemodynamic conditions, sufficient sedation and analgesia, and acceptable apnea with desaturation.